2016
DOI: 10.1038/srep24393
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis and all-cause mortality in worldwide populations: grading the evidence from a meta-analysis

Abstract: The objective of this study is to investigate the association between osteoarthritis (OA) and all-cause mortality in worldwide populations and to develop recommendations according to GRADE evidence levels. Literature search through Nov 2015 was performed using the electronic databases (including MEDLINE, EMBASE, EBSCO and Cochrane library). The prospective cohort trials that investigated the association between the symptomatic OA (SxOA) or radiological OA (ROA) and all-cause mortality were identified. Hazard r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 24 publications
3
73
2
Order By: Relevance
“…Consistent with other studies, we found no increase in mortality risk in patients with knee or hip OA, although this was not the primary outcome for our study 34,35 .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with other studies, we found no increase in mortality risk in patients with knee or hip OA, although this was not the primary outcome for our study 34,35 .…”
Section: Discussionsupporting
confidence: 91%
“…A 2008 review suggested modest associations of OA with all-cause mortality but noted that technical shortcomings limited their conclusions, including differing study populations, small sample size and lack of inclusion of important covariates from some of the studies 12 . A more recent meta-analysis of nine studies reported no significant association between radiographic osteoarthritis (rOA) or symptomatic OA (SxOA) with mortality, however this study also did not differentiate between joint sites affected by OA, combining estimates for hand, knee, hip and spine OA 13 . Prospective studies addressing knee OA specifically as a risk factor for premature mortality have been equivocal with some reporting lower mortality among those with knee OA 14e16 and others reporting higher mortality rates 17e19 .…”
Section: Introductionmentioning
confidence: 73%
“…Several studies have also assessed the relation of knee OA to the risk of mortality 49 . Although findings are inconclusive, a few recently published studies have reported that knee symptomatic OA (SxOA) was associated with a high risk of all-cause mortality 46 .…”
Section: Introductionmentioning
confidence: 99%